The Hedge Fund Industry since the Global Economic Crisis of 2007-2009. Have Global Hedge Funds Put their Money where their Mouth is? - Wiśniewski, Piotr (Sektor funduszy zabezpieczających po globalnym kryzysie z lat 2007-2009. Czy fundusze zabezpieczające spełniły swoje zadanie?, 2011)
The hedge fund industry represents a significant and viable alternative for mainstream investment business clientèle, as well as a growing number of sophisticated high net worth individuals. The hedge fund raison d’être has been relative independence of other (more traditional) asset classes and competitive return/risk characteristics. Although the global hedge fund community is still reeling from the turmoil of 2007-2009, it is not premature for a preliminary assessment of hedge funds’ performance during and post the recent global financial crisis. Early indications offer a mixed perspective. On the one hand, the hedge fund community as a whole showed considerable resilience to the global financial turmoil, on the other – its risk adjusted value creation success has been rather mediocre.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 158, s. 1099-1110
Keywords: alternative asset management; hedge fund performance and efficiency; global financial crisis of 2007-2009